Adjustment Strategies for Marital Stress Among Female Teachers in Nigeria: Implications for Counselors - Odebode, Aminat Adeola; Ola-Alani, Eniola Keji; Gambari, Shakirat Ojuolape (Universitas Negeri Semarang, 2019)
Stress have devastating consequences when not well managed. This study thus investigated the adjustment strategies of marital stress among female primary school teachers in Nigeria. The study also examined the influence of age, number of children, type of marriage and length of years in service on the respondents’ views. The study employed a descriptive survey method. A total of 422 female primary school teachers participated in the study. The participants responded to a researcher-designed instrument titled ‘Adjustment Strategies Questionnaire (ASQ)’. The data were analyzed using both percentage, mean, t-test and Analysis of Variance The result showed that female primary school teachers adopt benefitting adjustment strategies. Result further showed that there were significant differences based on age, number of children, type of marriage and length of years in marriage. Recommendations were therefore made among others that counselors should encourage female primary school teachers to maintain their benefitting adjustment strategies of marital stress.